Adoption of an activity based costing model in an Indian steel plant - Dwivedi, Rishi; Chakraborty, Shankar (Business: Theory and Practice, 2016)
In the age of relentless global competition, constantly improving technology and better information systems, managers are often compelled to devise new strategies to maintain sustained competitive advantage while adopting new business management approaches. So, in this paper, an activity based costing (ABC) model is proposed for a raw material handling section of an Indian steel plant. The results obtained from ABC model application in the said department facilitates quantification of the unit cost of each process, analysis of various activities in order to identify inefficiency, setting-up of better budget allocation, initiation of cost minimization procedure and establishment of an efficient resource requirement plan. Moreover, the cost information derived from ABC model is compared with that extracted from the traditional costing system to demonstrate that ABC model can significantly minimize the product cost distortion resulting from unsystematic allocation of overhead costs. This paper also discusses the practical implication of the implemented ABC model with respect to its critical role in effective resource control, improved strategic and operational decision making, and aid in continuous improvement through internal cost minimization in the department.